Asymmetric impact of real exchange rate on inflation in Ethiopia: A non-linear ARDL approach - Samuel Elias Kayamo (Cogent Economics & Finance, 2021)
A surge in inflation for the last decade has been a top agenda of political and economic debate in Ethiopia. The monitory authority of the country has regularly devalued Ethiopian birr to stabilize the inflation and stimulate exports. Whether this has indeed stabilized inflation and increased export earnings is an issue of debate. This study investigates the asymmetric impact of real exchange rate on inflation for period 1982-2019. The non-linear ARDL bounds test is used to test the presence of long-run co-integrations. Long- and short-run estimations were done based on the non-linear ARDL error correction methodology. The result of the study indicated that the real exchange rate has asymmetric effects on inflation in short- and long-run. The imbalance in real exchange rate (depreciation and appreciation) causes a surge in inflation in the long-run. The policy implication of this study is that flexibility in exchange rate market should be planned to ensure price stability rather than following restrictive exchange rate policy.
Keywords: 330; Ethiopia; inflation; non-linear ARDL; real exchange rate